OpenMP Performance in Numerical Simulation of Dambreak Problem Using Shallow Water Equations - Gunawan, Dr. Putu Harry (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 11 No 1 (2020): Vol. 11, No. 1 April 2020DO - 10.24843/LKJITI.2020.v11.i01.p01, 2020)
Numerical simulation of water surface waves is widely used to describe water flow and its impact for human life. For instance, numerical simulation of waves is elaborated to simulate Tsunami as an early warning system. Using numerical approach, the study of water flow will reduce cost and save time compared with the conventional approach (in laboratory). Shallow water equations (SWE) is one of the mathematical models which can be used to describe water flow. In numerical simulation of SWE, finite volume method is a robust method to approximate SWE. The result using numerical approach depends on the number of grids. High number of grids then smooth solution can be obtained. However, increasing number of grids leads to the increasing of computational cost. In this paper, parallel computing using OpenMP platform is given in order to reduce computational cost of numerical simulation. In parallel computing performances, Speedup and Efficiency of numerical simulation using 6400 grids points are obtained 4 times and 51% respectively. Moreover, by several numbers of cores from 2 to 8, CPU time of parallel computing is shown decreasing along the increasing number of computer cores.